SURONO'S CROSS-STYLED CREATION IN THE SHADOW PUPPET PERFORMANCE - Chatur Rhama; Tatik Harpawati (ISI Press Institut Seni Indonesia Surakarta, 2023)
Surono Gondo Taruno's shadow puppet (wayang kulit) performance has a distinctive cross-style, making him a famous puppeteer in East Java. Accordingly, this discussion seeks to answer the question,